Application of the Project Based Learning (PjBL) Learning Model to the Skills of Making Vertical Gardens for Class 4 Students at SDN Durungbedug - Rizkita, Ika Wahyu; Ummah, Fiena Saadatul; Kusminarsih, Titin; Wardani, Nur Afni Ayu (EduLine: Journal of Education and Learning Innovation, 2025)
Skills are an important skill for someone to have to face problems, especially in the 21st century era. Sharpening skills needs to be done from an early age and can be done through various efforts. The aim of this research is to determine the extent to which the implementation of the Project Based Learning (PjBL) learning model has improved the skills of grade 4 students at SDN Durungbedug in making vertical gardens. The method used in this research is Classroom Action Research (PTK) with a quantitative approach. The data collection techniques used were tests and observations with data analysis in the form of quantitative descriptive analysis. The subjects in this research were 4th grade students at SDN Durungbedug. The results of the research showed that 6 students got grades with sufficient criteria and 9 students got grades with good criteria in cycle 1, while in cycle 2 it was found that 3 students got grades with good criteria and 12 students got grades with very good criteria. From these results it can be concluded that the application of the Project Based Learning (PjBL) learning model with a project in the form of creating a vertical garden and recycled pots as a planting medium can improve students' skills.